On Averting Negative Emotion: Remedying the Impact of Shifting Expectations - Cho, Cecile K.; Cho, Theresa S. (Frontiers in Psychology, 2018)
This paper examines how people anticipate negative emotion when faced with an uncertain outcome and try to manage their expectation. While extant research streams remain equivocal on whether managing expectation always succeeds, this research examines situations in which setting a low expectation can have an adverse emotional impact and ways to alleviate this negative emotional consequence. Using goal setting and false-feedback paradigm, we show that those who set low goals to manage expectation can end up feeling more disappointed than those who set high goals (study 1), but this negative impact can be avoided when goals are reminded at feedback and when individuals are made aware of the inaccuracies in forecasting affect or are reminded of their initial goal (studies 1 and 2).